2007
DOI: 10.1007/s12039-007-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

A concise review of dynamical processes in polymorphic environments of a block copolymer: Rotational diffusion and photoisomerization

Abstract: This article describes our ongoing efforts to understand dynamical processes such as rotational diffusion and photoisomerization in polymorphic environments of a block copolymer. The objective is to explore how the typical properties of a block copolymer solution such as critical micelle temperature (CMT) and temperature-induced sol-gel transition influence the rotational diffusion of hydrophobic solute molecules. Rotational diffusion of solute molecules differs significantly below and above the CMT of a block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…37 Along with the change in polarity during sol-gel transition of pluronics viscosity of the medium also change appreciably. [1][2][3][4] So, it is necessary to verify the effect of medium viscosity on the uorescence properties. Glycerol and ethylene glycol have been chosen which are known to undergo change in viscosity with change in temperature to verify the viscosity effect on uorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Along with the change in polarity during sol-gel transition of pluronics viscosity of the medium also change appreciably. [1][2][3][4] So, it is necessary to verify the effect of medium viscosity on the uorescence properties. Glycerol and ethylene glycol have been chosen which are known to undergo change in viscosity with change in temperature to verify the viscosity effect on uorescence.…”
Section: Resultsmentioning
confidence: 99%
“…2 A more pronounced temperature effect on PPO solubility over PEO imparts amphiphilicity to pluronics. 3,4 Thus, these block polymers form micelle followed by gelation both as a function of temperature and concentration, unlike conventional surfactants. Anhydrous hydrophobic core region of the spherical micelle consists of PPO units helps in solubilization of water insoluble drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Using fluorescence anisotropy measurements, Dutt et al have recently reported on the rotational dynamics of a solubilized probe in different phases of pluronic micelles. [31][32][33][34][35] Grant et al have demonstrated from anisotropy measurements that a suitable molecular probe can be used as a local reporter for the different regions of the copolymer micelles. 36,37 Relaxation of the water molecules in different regions of pluronic micelles have recently been reported by Bhattacharya et al [38][39][40] and Kumbhakar et al [41][42][43] All these studies indicate that the dynamical processes in these micelles largely depend on the EO and PO ratios of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…33 These polymers possess amphiphilicity due to the temperature induced preferential solubility of one unit over another. 34,35 As a result, they form spherical micelles and gels, as a function of both temperature and concentration. 36,37 The highly hydrophobic anhydrous inner core region of these micelles helps in solubilizing water insoluble drug molecules.…”
Section: Introductionmentioning
confidence: 99%